STRATEGIES AND THE ROLE OF TEACHERS IN CLASSROOM MANAGEMENT TO IMPROVING THE EFFECTIVENESS OF LEARNING AT THAUTHIATUT THULAB SECONDARY SCHOOL (Al-Mubin, 2025)
This study aims to provide an in-depth description of the role of teachers in classroom management at Thauthiatut Thulab Junior High School. Classroom management is a crucial factor in creating a conducive and effective learning environment that supports the achievement of learning objectives. At lower secondary school (SMP) level, the implementation of good classroom management becomes increasingly important as pupils are in a transitional phase towards adolescence, characterised by emotional, social and behavioural changes. Therefore, teachers are required to have the ability to manage the classroom so that the learning process can take place in an orderly and productive manner. This study employed a descriptive qualitative method, with data collected through observation and interviews with teachers and relevant stakeholders. The findings indicate that teachers act as managers, facilitators and mediators of learning, capable of integrating the values of student discipline into classroom activities. These roles contribute to creating a learning environment that is orderly, comfortable and supportive of students’ character development and academic achievement.